Microstructure and electrical properties of SiC dispersed molybdenum silicide composite. (26th May 2016) - Byun, J. M.; Bang, S.-R.; Kim, S. H.; Kim, Y. D.
Abstract : In this study, a core–shell composite powder with Mo as the shell material and β-SiC as the core material was produced via chemical vapour transport caused by the hydrogen reduction of Mo oxide. Using this core–shell composite powder, a Mo silicide composite with uniformly dispersed β-SiC was fabricated by pressureless sintering at 1400°C. The relative density of specimens sintered for 10 hours was 96.1% and the electrical resistivity was 4.68 × 10 −5  Ω m. It was concluded that a β-SiC dispersed molybdenum silicide composite with enhanced electrical resistivity was successfully fabricated at a relatively low sintering temperature using the core–shell composite powder.